THE IMPACT OF DOOR NUMBER ON DURATION OF BOARDING PROCEDURE - Hromadka, Martin (Doprava a spoje, 2012)
This paper assesses the possibility of combined passenger boarding using both airbridge with the front aircraft door and the mobile stairs with the rear door at the concrete airport in order to shorten the boarding time.